How does tolerability of double balloon enteroscopy compare to other forms of endoscopy?. Issue 1 (18th March 2015) - Irvine, Andrew J; Sanders, David S; Hopper, Andrew; Kurien, Matthew; Sidhu, Reena
Abstract : Background and aims: Gastrointestinal endoscopy can be difficult for patients to tolerate. Studies on endoscopic tolerability mainly focus on gastroscopy or colonoscopy with a paucity of data on double balloon enteroscopy (DBE). We aimed to prospectively evaluate tolerability in patients undergoing several forms of endoscopy including DBE. Methods: Consecutive patients undergoing colonoscopy, flexible sigmoidoscopy, gastroscopy, endoscopic retrograde pancreatography (ERCP), capsule endoscopy (CE) and DBE were prospectively recruited. A questionnaire recorded demographics, procedural data, patient tolerability (pain, discomfort and distress recorded on numerical rating scales) and the Hospital Anxiety and Depression Scale (HADS). Results: 956 patients were recruited (512 women; median age 57 years). The median pain score for DBE was poor with a score of 5 compared with 1 and 0 for oesophagogastroduodenoscopy and ERCP, respectively (p<0.001). Colonoscopy and retrograde DBE scores were not dissimilar. CE was well tolerated with a median pain score of 0. Patients with DBE required significantly higher doses of sedation and analgesia than other patients. The HADS Anxiety Score was also associated with poorer tolerability. Conclusions: DBE is poorly tolerated when compared with other forms of endoscopy despite higher doses of sedation. Increasing demand to improve tolerability of DBE in the UK may be addressed with the use of propofol.